Association between blood lead levels and hyperlipidemiais: Results from the NHANES (1999-2018) - Yangchang Zhang; Yangchang Zhang; Yangchang Zhang; Yangchang Zhang; Weiwei Liu; Weiwei Liu; Weiwei Liu; Wei Zhang; Rui Cheng; Andi Tan; Shisi Shen; Yang Xiong; et al. (Frontiers Media S.A., 2022)
BackgroundResearch on the association between blood lead (Pb) and lipid biomarkers have yielded inconsistent results, and epidemiological studies on blood Pb levels and hyperlipidemia are scarce. The present study aimed to examine the association between blood Pb levels and hyperlipidemia in adults from the National Health and Nutrition Examination Survey (NHANES).MethodsA total of 43,196 participants in the NHANES from 1999 to 2018 were included in the final analysis. Hyperlipidemia was determined based on the National Cholesterol Education Program guidelines. Blood Pb levels were assessed using inductively-coupled plasma mass spectrometry. Weighted multivariable logistic regression analysis and subgroup analysis were conducted to determine the correlation between blood Pb levels and hyperlipidemia.ResultsIn the multivariable logistic regression model, high blood Pb levels were significantly associated with hyperlipidemia after adjusting for confounders (OR 1.41; 95%CI: 1.18-1.67). Furthermore, elevated blood Pb levels were associated with an increased risk of hyperlipidemia across the four quartile (Q) groups (Q1: OR 1.00; Q2: OR 1.16 [95%CI: 1.04-1.29]; Q3: OR 1.39 [95%CI: 1.21-1.59]; and Q4: OR 1.33 [95%CI: 1.15-1.54]; P for trend <0.05). Significant moderating effects were found in the subgroup analysis stratified by age, education, hypertension, and diabetes (P < 0.05). In sensitivity analysis, the ORs for hyperlipidemia across the quartiles of blood Pb levels were 1.00, 1.17 (95%CI: 1.05-1.30), 1.42 (95%CI: 1.24-1.62), and 1.38 (95%CI: 1.19-1.60) for Q1, Q2, Q3, and Q4, respectively (P for trend <0.001) after removing adults with arteriosclerotic cardiovascular disease, and the ORs were 1.00, 1.13 (95%CI: 1.01-1.25), 1.38 (95%CI: 1.21-1.56), and 1.32 (95%CI: 1.16-1.52) for Q1, Q2, Q3, and Q4, respectively (P for trend <0.001) after including pregnant women.ConclusionThe current study showed a positive association between blood lead levels and hyperlipidemia.